(untitled) (International Journal of Food and Nutritional Sciences, 2023)
In this project, we propose a cloud-based real-time human activity recognition system. First, we develop a wearable system that contains an Accelerometer sensor, Heart beat sensor, an Arduino and a WIFI module in order to sense human movement and heart rate of human body. Whatever the data created stored in cloud using Internet of things (IOT). And also display the data in Lcd display. If the Heart beat increases due to any Health issue the buzzer rings automatically, which help for easy Notification. The proposed system is able to achieve an average of 93% accuracy in classifying the different activities efficiently.